The Developing of Rhetoric and Grammar by Using Grammarly Chrome at SMAN 3 Lembar Academic Year 2020/2021 - Jupri Jupri (Humanitatis : Journal of Language and Literature, 2021)
The purpose of this study is to know whether using Grammarly Chrome is able to increase students’ rhetoric and grammar competence in constructing the report text writing. The method of study used is class action research (CAR) which consists of two cycles and each of them has four steps such as planning, action, evaluation, and reflection. This study focuses on students’ competence in constructing an English report text. The data collected method is the students’ worksheet result after getting the treatment of the teaching-learning process with Grammarly Chrom's help. The result of study indicated that there was a significant increase in student’s competence in terms of constructing the report text. In the 2nd cycle is found the students’ worksheet result average is 85, and there were about 95% of students has achieved a score ≥ of 75. While in the 1st cycle is found the students’ average is 77, and there was 63% of students have achieved a score ≥ of 75. And students respond in using Grammarly Chrome is found significantly interested which’s about early 18 students actively followed the process of teaching learning in the 1st cycle, while in the 2nd cycle students who interested increased into 22 students, based on the data, the using Grammarly Chrome may increase students’ rhetoric and grammar competence, it could give positive influence in terms of constructing an English writer of the report text.